2019
DOI: 10.1111/pbi.13207
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the interactions between a plant‐produced HIV antibody and human Fc receptors

Abstract: Plants can provide a cost-effective and scalable technology for production of therapeutic monoclonal antibodies, with the potential for precise engineering of glycosylation. Glycan structures in the antibody Fc region influence binding properties to Fc receptors, which opens opportunities for modulation of antibody effector functions. To test the impact of glycosylation in detail, on binding to human Fc receptors, different glycovariants of VRC01, a broadly neutralizing HIV monoclonal antibody, were generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 88 publications
5
32
1
1
Order By: Relevance
“…In an SPR assay measuring binding of soluble FcγRIIIa to N6 on the solid phase, there was almost one log difference in a nity between pN6 (K D 6.439 × 10 − 8 M) and mN6 (K D 8.577 × 10 − 7 M). As observed elsewhere, the difference in a nity was largely due to a difference in the dissociation constant K d (31).…”
Section: Antibody-dependent Cellular Cytotoxicity Activationsupporting
confidence: 69%
See 2 more Smart Citations
“…In an SPR assay measuring binding of soluble FcγRIIIa to N6 on the solid phase, there was almost one log difference in a nity between pN6 (K D 6.439 × 10 − 8 M) and mN6 (K D 8.577 × 10 − 7 M). As observed elsewhere, the difference in a nity was largely due to a difference in the dissociation constant K d (31).…”
Section: Antibody-dependent Cellular Cytotoxicity Activationsupporting
confidence: 69%
“…We and others have shown that IgG mAbs bearing N-glycan fucosylation at either the α-1,6 position (in mammals) or the α-1,3 (in plants) have reduced binding a nity to the low a nity FcγRIIIa (CD16a) receptor(31) , (56)(57)(58)(59) which is found on natural killer cells, neutrophils and monocytes. Expressing an IgG mAb in the ΔXF N. benthamiana line was shown to restore the interaction with FcγRIIIa receptor (31). Antibody binding to FcγRIIIa is associated with antibody dependent cellular cytotoxicity (ADCC), an effector mechanism that enhances killing of virally infected cells by these immune cells (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of plant-produced versions of some of these antibodies has been tested in animal trials 7 . A remarkable achievement is the generation of Abs with engineered Fc glycosylation resulting in similar or increased Fc receptor binding activities compared to the non-glycoengineered mammalian cell-derived variants [15][16][17] .…”
mentioning
confidence: 99%
“…Although other antibodies have shown better performance, this plant-made antibody cocktail has revealed the potential of the technology in the fight against emerging diseases [15]. Today glycoengineering approaches are available to yield specific antibody glycoforms, which will allow optimizing the functional activity and safety of the target antibodies [16]. Moreover, functional single chain antibodies are also produced in plant systems; providing simpler molecules for viral neutralization [17].…”
Section: Molecular Farming: a Mature Technologymentioning
confidence: 99%